Pentingnya Kebutuhan Regulasi Kualifikasi Trustee Individu Setelah Pemberlakuan Undang-Undang Nomor 4 Tahun 2023 - Apsarini, Fairuz Larissa; Shinta Puspita Sari (RechtJiva, 2026)
This study discusses the urgency of regulating the qualifications of individual trustees after the enactment of Article 34 paragraph of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (P2SK Law), which opens up opportunities for individuals to act as trustees, but has not been accompanied by implementing regulations as mandated by Article 39, thus creating a legal vacuum and uncertainty in trustee practices. This study aims to analyze the urgency of regulating the qualifications of individual trustees in the P2SK Law. The study uses a normative juridical method with a legislative and conceptual approach, with legal materials analyzed descriptively through grammatical interpretation of relevant national and foreign provisions. The results of the study show that philosophically, this regulation is a manifestation of the 2nd and 5th principles of Pancasila to ensure fair treatment and legal protection for the community. Sociologically, the increasing complexity of the financial sector and the need for professional asset management require regulations that can protect the interests of settlors and beneficiaries. Juridically, Article 34 paragraph (3) of the P2SK Law, which allows individuals to become trustees, namely individuals appointed to manage trust assets for beneficiaries with assets separate from their personal property, will become non-executable and create a legal vacuum. Therefore, a Government Regulation is needed as a legal umbrella that delegates technical regulations to the Financial Services Authority (OJK) to form a special POJK regarding individual trustees in order to create legal certainty and protection for all related parties.